Unraveling the impact of public debt on economic dynamics in Southeast Asia: A vector analysis perspective - Viphindrartin, Sebastiana; Lestari Widarni, Eny; Niken Wilantari, Regina; Apriono, Markus; Bawono, Suryaning (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2023)
This research employs a panel vector model to analyze panel data, examining the relationship between public debt, economic growth, interest rates, consumption, and net exports in Southeast Asia from 1990 to 2020. This quantitative study focuses on vector analysis using secondary data from the World Bank for the specified period. The findings reveal that public or state debt significantly inhibits most economic variables, suggesting a detrimental impact on Southeast Asia. A notable observation is the effect of rising interest rates on net exports, highlighting how increased rates hinder the exports of ASEAN member countries. Contrary to expectations, the analysis indicates that government spending escalates public debt. Furthermore, Southeast Asian consumption appears to bolster exports through international trade agreements. Interestingly, exports are found to increase government spending, implying a contribution to state revenues. A key finding is that economic growth, marked by GDP increases, positively influences all variables in this study, signifying that GDP growth spurs both the monetary and real sectors of the Southeast Asian economy.